Designing a national restaurant inspection disclosure system for New Zealand - Filion, Katie (Kansas State University, 2010)
The World Health Organization estimates that up to 30% of individuals in developed countries become ill from food or water each year, with up to 70% of these illnesses estimated to be linked to food service. Restaurant inspections aim to prevent restaurant-associated foodborne outbreaks while enhancing consumer confidence in the safety of food prepared in these establishments. Inspection disclosure systems have been developed as a tool for consumers and incentive for foodservice operators. Disclsosure systems are common in developed countries; however, they are inconsistent. Previous research has not determined the best format to disclose inspection results to the public while providing incentives for operators. This research aimed to develop a consistent, compelling and trusted disclosure system for New Zealand. The research evaluated existing disclosure systems operating internationally and nationally. The national review interviewed with Environmental Health Officers (EHOs)(n=8), operators (n=109) and consumers (n=244), and findings were used for card designs. Cards were evaluated internally (n=43), then by 11 focus groups (n=68). Two cards, letter and gauge, were introduced to food premises (n=371) in six districts for three months for evaluation. Operators (n=269) and consumers (n=991) were interviewed to determine which design best communicated inspection results. The majority of operators indicated they had not received consumer feedback about the card, and half felt the card was something consumers would use. Less than half of consumers indicated they noticed cards prior to entering a premises; from these data it appeared the letter attracted more initial attention (78% of respondents) than the gauge (45%). Consumers indicated card placement was an important factor in noticing cards. Nearly all interviewed consumers indicated they expected cards at restaurants, take-aways and fish n’ chips shops. When asked which card they preferred, 58% (n=38) of operators with the gauge preferred the letter; and 79% (n=47) of operators with the letter preferred the letter. Consumer preference was for the letter, with 88% (n=133) of those in gauge districts preferring the letter, and 72% (n=161) of those in letter districts preferring the letter. Based on these data the letter card was recommended for a national inspection disclosure system for New Zealand.
Keywords: Restaurant; Hygiene; Inspection; Grading; Foodservice; Disclosure; Agriculture, Food Science and Technology (0359)